2021
DOI: 10.1194/jlr.ra120000950
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sphinganine is selectively assimilated by members of the mammalian gut microbiome

Abstract: Functions of the gut microbiome have a growing number of implications for host metabolic health, with diet being one of the most significant influences on microbiome composition. Compelling links between diet and the gut microbiome suggest key roles for various macronutrients, including lipids, yet how individual classes of dietary lipids interact with the microbiome remains largely unknown. Sphingolipids are bioactive components of most foods and are also produced by prominent gut microbes. This makes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 61 publications
2
37
0
Order By: Relevance
“…Differences in hepatic and serum lipids have been previously observed to be diet and microbiota dependent [26,[29][30][31][32] and plasma lipids are well known to be directly influenced by dietary lipids [33][34][35][36]. Similar to a previous study, we observed more differential lipid molecules between conventional and germfree in the liver compared to plasma [26].…”
Section: Discussionsupporting
confidence: 89%
“…Differences in hepatic and serum lipids have been previously observed to be diet and microbiota dependent [26,[29][30][31][32] and plasma lipids are well known to be directly influenced by dietary lipids [33][34][35][36]. Similar to a previous study, we observed more differential lipid molecules between conventional and germfree in the liver compared to plasma [26].…”
Section: Discussionsupporting
confidence: 89%
“…Intriguingly, using cell culture, they showed that microbially-derived SPs are incorporated into mammalian SP pathways. More recently, Lee et al charted the pathways of dietary SPs in the gut microbiome ( Figure 1 ) [ 40 ]. Taking the Bioorthogonal labeling-Sort-Seq-Spec (BOSSS) approach, the authors found that dietary SPs were mainly consumed by Bacteroides.…”
Section: Synthesis Of Lipids By Gut Microbesmentioning
confidence: 99%
“…Taking the Bioorthogonal labeling-Sort-Seq-Spec (BOSSS) approach, the authors found that dietary SPs were mainly consumed by Bacteroides. They also found that Bifidobacterium , which do not produce SPs, could process dietary SPs in a manner similar to that of SP-producer Bacteroides , suggesting that bioactive lipids which are metabolically-accessible to the gut microbiome could be the target for the host to control its gut microbial composition [ 40 ].…”
Section: Synthesis Of Lipids By Gut Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal, bioorthogonal click chemistry was cleverly used by Lee et al. ( 11 ) to interrogate the metabolism of sphinganine in the gut microbiome using a strategy that advanced the utility of click chemistry by incorporating flow cytometry and rRNA sequencing into their workflow. This study exploited several key features of click chemistry tools through a protocol that the authors describe as BioOrthogonal-Sort-Sequence-Spectrometry (BOSSS).…”
mentioning
confidence: 99%